Keselamatan yang Tak Sama: Laki-laki Lebih Diutamakan, Perempuan Lebih Dilupakan - Adalia Samaira Nanrimansyah; Iman Ahmad Gymnastiar (Konsensus : Jurnal Ilmu Pertahanan, Hukum dan Ilmu Komunikasi, 2025)
Gender inequality in terms of safety in public spaces is a crucial issue in Indonesia. This research background is driven by the high rate of violence against women, reaching 330,079 cases in 2024, and reinforced by a patriarchal culture that perpetuates gender hierarchy. This study uses a qualitative method with a literature study approach to analyze the root causes and impacts of gender inequality on women's sense of security in public spaces. The results indicate that the disparity manifests in various dimensions, such as women-unfriendly urban infrastructure (e.g., inadequate lighting), security threats in urban areas, and the high rate of gender-based violence where 80.1% of the victims are women. The discussion reveals that this inequality impacts not only physical safety but also psychological well-being, economic security, and access to public spaces. This research concludes that a multidimensional approach encompassing infrastructure improvement, strengthening legal protection, changing social norms, and economic empowerment is required to create an inclusive, equitable, and safe public environment for all genders.